An epidemiological survey of the time and sequence of eruption of permanent teeth in 4–15-year-olds in Tehran, Iran - M. MOSLEMI (Paediatric Dentistry, 2004)
The aims of this study were to define the average time of eruption of permanent teeth, the range of variation of the eruption time of each tooth, and their sequence of eruption amongst boys and girls in Tehran, Iran.